Time trends in radiocaesium in the Japanese diet following nuclear weapons testing and Chernobyl: Implications for long term contamination post-Fukushima - Smith, Jim T.; Tagami, Keiko; Uchida, Shigeo (The Science of the total environment, 2017)
Estimation of time changes in radiocaesium in foodstuffs is key to predicting the long term impact of the Fukushima accident on the Japanese diet. We have modelled >4000 measurements, spanning 50 years, of 137Cs in foodstuffs and whole diet in Japan after nuclear weapons testing (NWT) and the Chernobyl accident. Broadly consistent long term trends in 137Cs activity concentrations are seen between different agricultural foodstuffs; whole diet follows this general trend with remarkably little variation between averages for different regions of Japan. Model blind tests against post-NWT data for the Fukushima Prefecture showed good predictions for radiocaesium in whole diet, spinach and Japanese radish (for which good long term test data were available). For the post-Fukushima period to 2015, radiocaesium in the average diet followed a declining time trend consistent with that seen after NWT and Chernobyl. Data for different regions post-Fukushima show a high degree of mixing of dietary foodstuffs between regions: significant over-estimates of average dietary 137Cs were made when it was assumed that only regionally-produced food was consumed. Predictions of mean committed effective internal doses from dietary 137Cs (2011 to 2061) in non-evacuated parts of the Fukushima Prefecture show that average internal dose is relatively low. This study focused on average regional ingestion dose rates and does not attempt to make site specific predictions. However, temporal trends identified could form a basis for site specific predictions of long term activity concentrations in agricultural products and diet both outside and (to assess potential re-use) inside currently evacuated areas. [Display omitted] 50years of radiocaesium in the Japanese diet. •Cs is the main contaminant following the Fukushima Daiichi nuclear accident.•We analysed >4000 measurements of Cs in Japan over 50years pre-Fukushima.•Time trends in changes in Cs in foodstuffs and diet were identified.•Relatively consistent time trends were seen in diet pre and post-Fukushima.•Models of 1959–2009 data can inform dose predictions and management.